MAPPING AMERICAN CRIMINAL LAW Variations Across the 50 States: Ch. 14 Insanity Defense - Robinson, Paul H. (2017)
It is common for criminal law scholars from outside the United States to discuss the “American rule” and compare it to the rule of other countries. As this volume makes clear, however, there is no such thing as an “American rule.” Because each of the states, plus the District of Columbia and the federal system, have their own criminal law, there are fifty-two American criminal codes.American criminal law scholars know this, of course, but they too commonly speak of the “general rule” as if it reflects some consensus or near consensus position among the states. But the truth is that the landscape of American criminal law is one of almost endless diversity, with few, if any, areas in which there is a consensus or near consensus. Even most American criminal law scholars seem to fail to appreciate the enormous diversity and disagreement among the fifty-two American jurisdictions.Unfortunately, there has been little work done to map this enormous diversity among the states, perhaps because it is an extremely burdensome project. Every legal issue requires a major research project investigating the criminal codes and caselaw of all fifty-two American jurisdictions. While the paucity of such diversity research is understandable, it is nonetheless regrettable, for it is the matters of disagreement that often point to the most interesting issues for scholars.In this first-of-its-kind volume, the authors sketch the extremely diverse legal landscape in the United States for a full range of criminal law doctrines. Beyond providing this mountain of research on the most important criminal law rules, the additional goals of the volume are, first, to raise awareness of the enormous diversity among the states and to document that diversity for a wide range of issues, to encourage criminal law scholars to investigate these and the many other points of disagreement that exist among the states, and to encourage legislatures to look to this new diversity scholarship and to the positions taken by other states when they set out to codify or recodify their criminal law (and to encourage judges to do the same in those jurisdictions that continue to allow judicial criminal law making).In each of the chapters, we examine a different area of American criminal law and identify the major groupings among the states on the primary issue in the area. Each chapter provides a map of the United States with each of the states visually coded according to its approach to the issue. The maps then often raise interesting hypotheses about geographic or other state factors that might explain the patterns of agreement and disagreement (red states versus blue states, rural versus urban, rich versus poor, West Coast versus East Coast, etc.). The last two chapters of the book illustrate how this mountain of research and the state groupings for each issue can be used by scholars in many disciplines – political scientists, criminologists, criminal law scholars, and sociologists, among others – to investigate hypotheses about why we see the patterns of agreement and disagreement that we see.Presented here is Chapter 14 of the book, concerning the insanity defense